Lower temperature electrochemical reduction of lunar regolith simulants in molten salts. (February 2022) - Meurisse, Alexandre; Lomax, Bethany; Selmeci, Áron; Conti, Melchiorre; Lindner, Robert; Makaya, Advenit; Symes, Mark D.; Carpenter, James
Abstract: Extraction of oxygen from lunar soil is key to the sustainability of human and robotic operations on the Moon and would open the path to in-space refuelling with space resources. This work investigates reducing the temperature of the electrochemical FFC process, by changing the salt from pure CaCl2 to eutectic mixtures with KCl, NaCl and LiCl. Initial experimental results demonstrate the feasibility of removing at least 40% of the oxygen present in lunar minerals in 24 ​h in all eutectics and at temperatures as low as 660 ​°C; 85% of the oxygen could be removed in the comparative experiment using the baseline conditions of CaCl2 at 950 ​°C. Besides the expected impact on the kinetics when running the process at lower temperature, parasitic reactions linked to the graphite anode's interaction with the extracted oxygen, calcium cycling between the electrodes, and other mechanisms specific to each salt mixture appear to have a significant impact on the reduction process. Further work is needed to understand the limiting factors for the reduction in each eutectic salt electrolyte. Highlights: The electro-reduction of lunar regolith simulant LMS-1 is demonstrated. LMS-1 is reduced in CaCl2, CaCl2 –KCl, CaCl2 –NaCl, CaCl2 –LiCl, and LiCl. The approach is based on the FFC-Cambridge process. Eutectic salt mixtures allowed to lower the process temperature down to 660 ​°C. More than 40% of the oxygen can be extracted in CaCl2 –LiCl eutectic at 660 ​°C.